Utility of Immunophenotypic Measurable Residual Disease in Adult Acute Myeloid Leukemia—Real-World Context - Patkar, Nikhil; Kakirde, Chinmayee; Bhanshe, Prasanna; Joshi, Swapnali; Chaudhary, Shruti; Badrinath, Yajamanam; Ghoghale, Sitaram; Deshpande, Nilesh; Kadechkar, Shraddha; Chatterjee, Gaurav; Kannan, Sadhana; Shetty, Dhanalaxmi; et al. (Frontiers in Oncology, 2019)
Introduction: One of the mainstays of chemotherapy in acute myeloid leukemia (AML) is induction with a goal to achieve morphological complete remission (CR). However, not all patients by this remission criterion achieve long term remission and a subset relapse. This relapse is explained by the presence of measurable residual disease (MRD). Methods: We accrued 451 consecutive patients of adult AML (from March 2012-December 2017) after informed consent. All patients received standard chemotherapy. MRD testing was done at post induction and if feasible post consolidation using 8 and later 10 colour FCM. Analysis of MRD was done using a combination of difference from normal and leukemia associated immunophenotype approaches. Conventional karyotyping and FISH were done as per standard recommendations and patients were classified into favorable, intermediate and poor cytogenetic risk groups. The presence of FLT3-ITD, NPM1 and CEBPA mutations was detected by a fragment length analysis-based assay. Results: As compared to western data, our cohort of patients was younger with a median age of 35 years. There were 62 induction deaths in this cohort (13.7%) and 77 patients (17.1%) were not in morphological remission. The median follow-up was 26.0 months. Poor risk cytogenetics & the presence of FLT3-ITD were significantly associated with inferior outcome. The presence of post induction MRD assessment was significantly associated with adverse outcome with respect to OS (p=0.01) as well as RFS (p=0.004). Amongst established genetic subgroups detection of MRD in intermediate cytogenetic and NPM1 mutated groups was also highly predictive of inferior outcome. On multivariate analysis immunophenotypic MRD at the end of induction and FLT3-ITD emerged as an independent prognostic factors predictive for outcome. Conclusion: This is the first data from a resource constrained real-world setting demonstrating the utility of AML MRD as well as long term outcome of AML. Our data is in agreement with other studies that determination of MRD is extremely important in predicting outcome. AML MRD is a very useful guide for guiding post remission strategies in AML and should be incorporated into routine treatment algorithms.